Formulation Development for Transdermal Delivery of Raloxifene, a Chemoprophylactic Agent against Breast Cancer - Deepal Vora; Amruta Dandekar; Sonalika Bhattaccharjee; Onkar N. Singh; Vivek Agrahari; M. Melissa Peet; Gustavo F. Doncel; Ajay K. Banga (MDPI AG, 2022)
Raloxifene (RLX) is a second-generation selective estrogen receptor modulator approved for the prevention of invasive breast cancer in women. Oral therapy of RLX requires daily intake and is associated with side effects that may lead to low adherence. We developed a weekly transdermal delivery system (TDS) for the sustained delivery of RLX to enhance the therapeutic effectiveness, increase adherence, and reduce side effects. We evaluated the weekly transdermal administration of RLX using passive permeation, chemical enhancers, physical enhancement techniques, and matrix- and reservoir-type systems, including polymeric gels. In vitro permeation studies were conducted using vertical Franz diffusion cells across dermatomed human skin or human epidermis. Oleic acid was selected as a chemical enhancer based on yielding the highest drug delivery amongst the various enhancers screened and was incorporated in the formulation of TDSs and polymeric gels. Based on in vitro results, both Eudragit- and colloidal silicon dioxide-based transdermal gels of RLX exceeded the target flux of 24 μg/cm2/day for 7 days. An infinite dose of these gels delivered 326.23 ± 107.58 µg/ cm2 and 498.81 ± 14.26 µg/ cm2 of RLX in 7 days, respectively, successfully exceeding the required target flux. These in vitro results confirm the potential of reservoir-based polymeric gels as a TDS for the weekly administration of RLX.